Maternal psychological distress and injury in the first year of life. (1st March 2011) - Spinks, A B; Cameron, C M; Scuffham, R A; Scott, R; Ng, S K; McClure, R
Abstract : Background: Many mothers of young children experience significant psychological distress which is associated with poor child health outcomes, including increased risk of injury. This research explores possible pathways through which maternal distress may influence injury occurrence in the first year of life. Method: The Environments for Healthy Living Study enrols pregnant mothers in a peri-urban area of Australia. Enrolled mothers complete surveys at recruitment (approximately 36 weeks gestation) and at 12 months postbirth to elicit information related to social, behavioural and health outcomes. Results: 1112 pregnant mothers were enrolled in the first 2 years of the study, and 857 (77%) returned a follow-up survey after 1 year. Responses indicated that 148 (17%) infants suffered an injury requiring medical attention in the first year. Mothers categorised with moderate to high psychological distress according to the Kessler 6 rating scale were more likely to report an injury than non-distressed mothers (p=0.028). Infant injury risk was also elevated among younger mothers and those who reported their child was difficult to care for, lower baseline ratings of community satisfaction or changes in parenting burden since the birth. Maternal psychological distress levels were influenced by a large number of social and demographic variables including relationship status, paternal education level, neighbourhood satisfaction, perceived financial difficulties and parenting burden. Conclusion: A number of personal, social and neighbourhood variables exist that may explain the demonstrated link between maternal psychological distress and injury in the first year of life.